Carboxymethyl cellulose is a superior polyanion to dextran sulfate in stabilizing and enhancing the solubility of amorphous drug-polyelectrolyte nanoparticle complex - Dong, Bingxue (2020)
Amorphous drug-polyanion nanoplex represents an effective solubility enhancement strategy of weakly-basic poorly-soluble drugs. While dextran sulfate (DXT) was chosen in most studies as the polyanion for nanoplex formation, drug-DXT nanoplex demonstrated poor long-term physical stability for drugs with high crystallization propensity, such as ciprofloxacin (CIP). Herein we hypothesized that amorphous form stability of CIP nanoplex could be improved by substituting DXT with carboxymethyl cellulose (CMC) known for its crystallization inhibiting activity. The optimal preparation condition of the CIP-CMC nanoplex was determined by investigating the effects of CMC/CIP charge ratio and pH on the resultant nanoplex's physical characteristics and preparation efficiency. At the optimal condition, the CIP-CMC nanoplex possessed size, zeta potential, and CIP payload of approximately 200 nm, -49 mV, and 76%, respectively. Its preparation was highly efficient with CIP utilization rate and overall yield of roughly 89% and 46%, respectively. Compared to the CIP-DXT nanoplex, the CIP-CMC nanoplex was larger and with higher CIP payload attributed to CMC's higher chain stiffness. The CIP-CMC nanoplex exhibited superior physical stability after twelve-month storage and improved solubility enhancement capability (30% higher), despite its slower dissolution. These results clearly established CMC as the superior polyanion to DXT for nanoplex formation of weakly-basic drugs.